CompTIA Security+ (SY0-601) Cert Prep: 10 Governance, Risk, and Compliance. - Chapple, Mike (linkedin.com, 2021)
This course covers what professionals need to know about cybersecurity governance and compliance issues to prepare for the Security+ exam.